The isolation of fusarium sporotrichioides from a diabetic foot wound sample and identification - (:unkn) unknown (My University, 2008)
Fusarium türleri bağışıklıkları baskılanmış hastalar için önemli fırsatçı patojenlerdir. Bu çalışmada, diyabetik ayaklı bir hastadan izole edilen patojenin, konvansiyonel ve moleküler tekniklerle tanımlanması yapılarak, Fusarium sporotrichioides olduğu sonucuna varıldı. HPLC analizleri, patojenin T-2 toksinini üretmediği görüldü. Dolayısıyla, laboratuvar tanılarında, Fusarium türleri basit çevresel kontaminantlar olarak düşünülmemelidir.

Fusaria are major opportunist pathogens for immunocompromised patients. In this study, it was concluded as a result of both conventional and molecular identification techniques that the isolate obtained from the patient’s diabetic foot was Fusarium sporotrichioides. T-2 toxin production of the pathogen was investigated using HPLC and no toxin determined. In laboratory diagnosis, it must not be thought that Fusaria are solely an environmental contaminant.
Diyabetik ayaklı bir hastaya ait yara örneğinden fusarium sporotrichioides izolasyonu ve tanımlanması
Keywords: Genel ve Dahili Tıp